Changes in intestinal barrier protein expression and intestinal flora in a rat model of visceral hypersensitivity. Issue 4 (25th November 2021) - Zhao, Li; Ren, Peipei; Wang, Miaolei; Wang, Jingjing; He, Xueyun; Gu, Jingyan; Lu, Yanyu; Wu, Yana; Liu, Junhong; Wang, Longde; Li, Hongfang
Abstract: Background: Destruction of the intestinal mucosal barrier and visceral hypersensitivity are main pathogenesis of irritable bowel syndrome (IBS). The study aimed to establish a rat model of visceral hypersensitivity and explore mechanisms involved the changes of the intestinal barrier protein expression and intestinal flora. Methods: A rat model of visceral hypersensitivity was established and evaluated using abdominal withdrawal reflex (AWR) scores, colonic paracellular permeability, and gastrointestinal motility. The expression of tight junction proteins, aquaporin proteins (AQPs), phosphorylated ERK, and proteinase‐activated receptor‐2 (PAR‐2) was determined. The intestinal microflora was evaluated by high‐throughput sequencing of the 16S rRNA gene. Key results: In model rats, AWR score and fecal water content were significantly increased, gastrointestinal motilities were disorder and characterized by an inhibition of gastric motility and an enhancement of small intestinal and colonic movement. The expressions of colonic occludin, ZO‐1, AQP3, and AQP8 were decreased but claudin‐2 and claudin‐4 were markedly increased. Imbalance of intestinal flora appeared and showed an obvious decrease of Lactobacillus and an increase of Clostridiales _bacterium. Additionally, the total serine protease activity in feces, the expressions of PAR2 and phosphorylated ERK in the colon tissues were increased significantly. Conclusion and inferences: The model rats of visceral hypersensitivity possess the decreased expression of occludin, ZO‐1, AQP3, AQP8, and the increased expression of claudin‐2 and claudin‐4, meanwhile develop an imbalance of intestinal flora which probably increase serine protease activity, thereby activating the PAR2/ERK signaling and causing the intestinal barrier disorder. Abstract : A model rat of visceral hypersensitivity related IBS‐D was established using acetic acid enema combined with restraint stress and tail‐clamping. After modeling, the abdominal withdrawal reflex (AWR) score, fecal water content, and colonic FITC‐dextran flux of the model rats were significantly increased, gastrointestinal motilities were disorder and characterized by an inhibition of gastric emptying, an enhancement of small intestinal and colonic movement, and an abnormality of gastrointestinal myoelectric activity. The expressions of colonic occludin, ZO‐1, AQP3, and AQP8 were decreased but claudin‐2 and claudin‐4 were markedly increased, so there occurred intestinal barrier disorder even diarrhea. Imbalance of intestinal flora appeared and showed an obvious decrease of Lactobacillus and an increase of Clostridiales _bacterium. Additionally, the total serine protease activity in feces, the expressions of PAR2 and phosphorylated ERK in the colon tissues were increased significantly.